Iraq : Diversified Development in a Resource-Rich Fragile State - World Bank (Washington, DC, 2015)
More than 10 years after the overthrow of Saddam, the impatience of the Iraqi people and government for transformation of their economy to advance shared prosperity is growing. The government has expressed the desire for the World Bank Group to enhance its role in this transformation. This note proposes two pillars for the government to consider as central to the objective of diversification: enabling transformative investments and a comprehensive financing framework aligned with these investments. The obstacles to this approach are considerable, so a pre-requisite is high level government ownership and an implementing structure to match. A proposed institutional structure to embody this is outlined.